The level of fatty acid-binding protein 4, a novel adipokine, is increased in rheumatoid arthritis and correlates with serum cholesterol levels - Andrés Cerezo, Lucie; Kuklová, Markéta; Hulejová, Hana; Vernerová, Zdeňka; Pešáková, Vlasta; Pecha, Ondřej; Veigl, David; Haluzík, Martin; Pavelka, Karel; Vencovský, Jiří; Senolt, Ladislav (Cytokine, 2013)
OBJECTIVE: To assess the expression of the novel adipokine Fatty Acid Binding Protein-4 (FABP4) in synovial tissues, serum and the synovial fluid of patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and to study the relationships among FABP4, disease activity and metabolic status. METHODS: FABP4 levels were measured in the serum and synovial fluid of 40 patients with RA and 40 control patients with OA. The disease activity score (DAS28), C-reactive protein (CRP) levels and serum lipids were assessed in patients with RA. Immunohistochemical analysis and confocal microscopy were used to study the expression and cell-specific distribution of FABP4 in synovial tissues. RESULTS: The age, sex and body mass index (BMI) adjusted levels of FABP4 were significantly higher in the serum (p=0.001) and synovial fluid (p=0.005) of patients with RA when compared to OA patients. FABP4 levels were higher in females than in males and correlated positively with body mass index (BMI) in patients with RA. Independent of confounders, FABP4 levels correlated with total cholesterol and LDL cholesterol in patients with RA, but not in OA patients. FABP4 levels were not affected by disease activity. Furthermore, the increased expression of FABP4 that was otherwise restricted to synovial fibroblasts, macrophages and B-cells was noted in RA patients at levels higher than that observed in OA patients. CONCLUSIONS: The observed elevation of FABP4 levels in RA patients and the positive correlation of the adipokine to cholesterol suggest that FABP4 may represent a potential link between RA and the increased risk of atherosclerotic changes.
Keywords: synoviální tekutina; Cholesterol; lidé; Middle Aged; cholesterol; Lipids; upregulace; fibroblasty; Rheumatoid arthritis; makrofágy; Female; B-lymfocyty; C-reaktivní protein; Synovial Fluid; Arthritis, Rheumatoid; Body Mass Index; Humans; osteoartróza; index tělesné hmotnosti; proteiny vázající mastné kyseliny; Inflammation; lidé středního věku; mužské pohlaví; Lipid profile; lipidy; ženské pohlaví; Fatty Acid-Binding Proteins; B-Lymphocytes; revmatoidní artritida; FABP4; Fibroblasts; Male; Osteoarthritis; C-Reactive Protein; Up-Regulation; Macrophages